Implementasi Gerakan Literasi Sekolah dalam Meningkatkan Kemampuan Membaca Siswa: (Studi Kasus Kelas 3 SDN 142 Hutabaringin) - Saridona Saridona (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
This study aims to determine how the implementation of the school literacy movement at SDN 142 Hutabaringin, to analyze the factors that influence the success of the school literacy movement in improving students' reading ability and to identify the challenges and obstacles that hinder the implementation of the school literacy movement at SDN 142 Hutabaringin. This study uses a qualitative approach and a phenomenon study research type. Data collection methods use observation, interviews, and documentation, data validity techniques use Source Triangulation and Technique Triangulation, data analysis uses the Data Reduction model, Data Presentation (Data Display), and Conclusion Drawing. The results of the study show that the implementation of the School Literacy Movement at SDN 142 Hutabaringin shows that students' interest in reading has increased significantly, especially in the habituation and development stages implemented by the school. The success factors of the School Literacy Movement at SDN 142 Hutabaringin are influenced by the policies implemented by school leaders to improve students' reading interest, the active role of teachers as facilitators of students in literacy at SDN 142 Hutabaringin. Challenges faced in implementing the School Literacy Movement at SDN 142 Hutabaringin include environmental factors that influence students' reading interest, which is predominantly focused on social media, and inadequate school facilities.